Echocardiographic evaluation of propranolol therapy for mitral valve prolapse - Winkle, Roger A. (1976)
This study evaluates the effect of propranolol on the echocardiogram of 8 patients with late systolic mitral valve prolapse. Echocardiograms were performed with the patients on no medication and again while on oral propranolol therapy. Propranolol caused a statistically significant increase in left ventricular volume; however, neither the echocardiographic pattern nor the timing of mitral valve prolapse was altered by propranolol. These findings suggest that factors in addition to left ventricular volume play a role in regulating valvular dysfunction in this condition.